Application of the Best Techniques to Reduce the Percentage of Storage Fungi in Peanut Seeds Arachis hypogaea - El-Gali, Zahra Ibrahim; El-Kadi, Magida Younis (Al-Mukhtar Journal of Sciences, 2020)
This study was conducted during the season 2019-2020 with the aim of testing the efficiency of some techniques to eliminate or reduce the frequency of storage fungi, namely Aspergillus flavus, A. niger, and Penicillium italicum naturally contaminating peanuts seeds. The seed sample was treated by soaking in hot water (50˚c, 60˚c, 70˚c), soaking in salt water at concentrations 10%, 15%, 20%, roasting in an ordinary oven at 150˚c for 10, 20 and 30 min, and roasting in a microwave oven at 100˚c for 1, 3, 5 and 7 min. The frequency of fungi occurrence percentage was estimated in seeds after treatments and incubation on the nutrient medium Potato Sucrose Agar (PSA). The results indicated the efficiency of all the techniques used in reducing the frequency of fungi in the treated seeds, as the fungus P. italicum was the most sensitive fungus under all techniques, and the study proved the superiority of the treatment by microwave roasting over the rest of the techniques, as it eliminated all the fungi carried in the seed by 100% when the duration of time used is 5 minutes.